Real-time imaging of enzymatic degradation of pretreated maize internodes reveals different cell types have different profiles. (June 2022) - Leroy, Amandine; Devaux, Marie-Françoise; Fanuel, Mathieu; Chauvet, Hugo; Durand, Sylvie; Alvarado, Camille; Habrant, Anouck; Sandt, Christophe; Rogniaux, Hélène; Paës, Gabriel; Guillon, Fabienne
Graphical abstract: Highlights: HWP increases heterogeneity of cell wall composition within the sample. HWP increases the enzymatic degradation of the pith parenchyma. Enzymes are not homogeneously distributed in the sample over time. Enzymes concentrate preferentially on cell walls richer in accessible cellulose. Heterogeneous distribution of enzymes leads to contrasted degradation profiles. Abstract: This work presents a dynamic view of the enzymatic degradation of maize cell walls, and sheds new light on the recalcitrance of hot water pretreated maize stem internodes. Infra-red microspectrometry, mass spectrometry, fluorescence recovery after photobleaching and fluorescence imaging were combined to investigate enzymatic hydrolysis at the cell scale. Depending on their polymer composition and organisation, cell types exhibits different extent and rate of enzymatic degradation. Enzymes act sequentially from the cell walls rich in accessible cellulose to the most recalcitrant cells. This phenomenon can be linked to the heterogeneous distribution of enzymes in the liquid medium and the adsorption/desorption mechanisms that differ with the type of cell.